2016
DOI: 10.17221/46/2015-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell structure, measurements, and quality-affecting factors in laying hens: a review

Abstract: Eggshell quality is one of the most significant factors affecting poultry industry; it economically influences egg production and hatchability. Eggshell consists of shell membranes and the true shell that includes mammillary layer, palisade layer, and cuticle. Measurements of eggshell quality include eggshell weight, shell percentage, breaking strength, thickness, and density. Mainly eggshell thickness and strength are affected by the time of egg components passage through the shell gland (uterus), eggshell ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
77
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 68 publications
3
77
1
5
Order By: Relevance
“…Hence, the production of heavier eggs in the HI50 group might explain the significant reduction in shell percentage and even in its thickness. Since the eggshell weight and thickness are physical variables correlated with the egg strength, resistance to physical and pathogenic challenges from laying to the transportation and selling phase [26], our results should be considered when evaluating the suitability to include the HI meal in the laying hens' feed.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the production of heavier eggs in the HI50 group might explain the significant reduction in shell percentage and even in its thickness. Since the eggshell weight and thickness are physical variables correlated with the egg strength, resistance to physical and pathogenic challenges from laying to the transportation and selling phase [26], our results should be considered when evaluating the suitability to include the HI meal in the laying hens' feed.…”
Section: Discussionmentioning
confidence: 99%
“…Mertens et al (2006) reported that shell strength was the greatest in aviary eggs and the weakest in free-range eggs. Inconsistent results explainable by structural differences of the eggshell are related to the interaction of the housing system, age, genotype, oviposition time, and mineral nutrition (Ketta and Tumova 2016).…”
mentioning
confidence: 98%
“…Very young birds with immature shell glands produce shell-less eggs or eggs with a thin eggshell (Ketta and Tumova 2016). Tumova et al (2014) detected a decreased eggshell strength in older hens in comparison with younger ones.…”
mentioning
confidence: 99%
“…In recent study Englmaierova et al (2015) confirmed that the shell quality of eggs that were laid by hens fed a diet with 1.8 g/kg of NPP and 350 FTU/kg of phytase Natuphos ® was comparable with the shell quality of eggs from hens that received a diet with only 2.1 g/kg of NPP. On the other hand, there is a lot of factors, both external and internal, affecting egg shell quality (Tumova et al 2014;Ketta and Tumova 2016;Skrivan et al 2016).…”
mentioning
confidence: 99%